Determinants of Financial Inclusion: A Study of Some Selected Districts of West Bengal, India - Kuri, Pravat Kumar; Laha, Arindam (Indian Journal of Finance, 2011)
Despite the current focus of policies devoted to enhancing access to finance in India, there is a shortage of information regarding actual access to finance. This paper attempts to measure the inter-state variations in the access to finance using a composite index of financial inclusion. Focusing on the level of financial inclusion, this paper identifies the underlying factors that are responsible for creating obstacles in the process of financial inclusion in rural West Bengal. Analysis based on Binary Probit Regression Model establishes that the greater degree of awareness of basic banking services, diversification of rural non-farm sector, literacy drive to rural households and an expansion of household level assets are some of the crucial factors which have significant bearings to create an enabling environment in reducing the obstacles in the process of financial inclusion. However, the land reform measures, which have created significant impact on landless, small and marginal farmers in West Bengal, especially in providing economic security, fail to augment the process of financial inclusion by bringing them in the network of financial services.